Beyond public reason liberalism: moderate perfectionism - Mang, F (2015)
Should the state undertake the task of promoting the good life? Perfectionism is the idea that the state should promote the good life. Many philosophers have answered in the negative to the above question, so they reject perfectionism. This thesis aims to develop a moderate version of perfectionism, and seeks to defend it against several influential anti-perfectionist arguments, in particular the argument from public reason liberalism. I begin by examining public reason liberalism. John Rawls, Gerald Gaus, Martha Nussbaum, and many other political philosophers endorse public reason liberalism. They believe that state coercion should be publicly justified, and that perfectionism cannot meet the requirements of public reason. I argue that public reason is the object of reasonable rejection, so it cannot be realised in actual politics through state intervention in a publicly justified way. In addition, I argue that respect for persons is not a reliable basis for public reason. Thus we have good reason to reject public reason liberalism. Then I develop a moderate version of perfectionism. I contend that the state should promote the good life through supporting a wide variety of perfectionist goods, and that it should do so by using moderate measures and by appealing to perfectionist judgements of a moderate kind. Some anti-perfectionists consider that perfectionism would be unnecessary when a fair distribution of resources is realised. Yet a fair distribution of resources is not foreseeable. I propose several kinds of moderate perfectionist policies that are of great importance for any neo-liberal society where the distribution of resources is far from fair, and these policies are ultimately important for the good life, not only for remedying unfairness. Contrary to the positions of many liberal philosophers including Ronald Dworkin and Jeremy Waldron, I argue that moderate perfectionism should not be rejected on grounds of paternalism and unfairness to different conceptions of the good.